Analisis Pengaruh Paenibacillus Polymyxa Terhadap Pertumbuhan Tanaman dan Unsur Hara Tanah Lahan Pascatambang Kapur - Larasati Kania Pramesti; M. Akbari Danasla (Pusat riset dan Inovasi Nasional, 2025)
Mining, especially open-pit mining, can have an impact on the environment and biodiversity. PT Semen Baturaja's limestone mining has an impact on the environment. Therefore, reclamation is necessary to restore the disturbed environmental conditions. The objective of this study is to analyze the effect of Paenibacillus polymyxa bacteria on post-limestone mining soil content and sengon plant growth in polybag media. This study uses an experimental method to observe the effect of treatment application. The treatments applied consist of three bacterial doses: 15 mL, 30 mL, and 45 mL. This study will observe sengon growth with the assistance of bacteria and manure fertilizer using polybag media. The parameters observed include soil pH, plant height, root length, as well as organic carbon (C-Organik), total nitrogen (N-Total), potential phosphorus (P Potensial), potential potassium (K Potensial), and Cation Exchange Capacity (CEC). The results of the study indicate that the application of Paenibacillus polymyxa bacteria can enhance soil nutrient content and support sengon plant growth. Soil nutrient content results show significant improvements in nutrient levels in former limestone mine soil. The best treatment was demonstrated by the 45 mL dose, which exhibited the highest increase in nutrient content.